Efektivitas Senam Ergonomik Terhadap Tekanan Darah Lansia Penderita Hipertensi Di Dukuh Banjarjo Kabupaten Malang - Verra Deafani Yuniar; Mizam Ari Kurniyanti; Muntaha Muntaha (Yayasan Jompa Research and Development, 2023)
One of the treatments for hypertension according to JNC 7 is physical activity. One of the physical activities that can be done by elderly people with hypertension is ergonomic gymnastics which are inspired by prayer moslem movements that are useful for restoring the position and flexibility of the nervous system and blood flow and maximizing the supply of oxygen to the brain, being able to maintain the body's freshness system, as well as being an exhaust system of negative energy from the body and control high blood pressure. The purpose of this study To find out the effectiveness of giving ergonomic exercises to the blood pressure of elderly people with hypertension. The method used a quasi experiment with pre-test and posttest control group design. The number of samples used was 18 respondents taken with the saturation technique which was divided into 8 respondents intervention group and 10 respondents control group. The bivariate test used were the Wilcoxon test and the Mann Whitney test. The results of the analysis showed that the average blood pressure in the intervention group before and after giving ergonomic exercises was systolic blood pressure 150,62 mmHg and 126,25 mmHg, in diastolic blood pressure 90,62 mmHg and 80,00 mmHg. It once the p-values ​​were 0.011 and 0.010 (<0.05), it means said that H1 is accepted and there is an effect of giving ergonomic exercises on blood pressure in elderly people with hypertension. The Conclusion of this study there is an effect of giving ergonomic exercises for 3 days on the blood pressure of elderly people with hypertension in Dukuh Banjarjo, Malang Regency